Community Perception towards Mental Illness among Residents of Gimbi Town, Western Ethiopia. (20th October 2016) - Benti, Misael; Ebrahim, Jemal; Awoke, Tadesse; Yohannis, Zegeye; Bedaso, Asres
Abstract : Background. Despite the increased burden of mental health problem, little is known about knowledge and perception of the public towards mental health problems in Ethiopia. Methods. Community based cross-sectional study was conducted among selected 845 Gimbi town residents from May 28 to June 28, 2014. Results. Out of the total study participants, 304 (37.3%) were found to have poor perception (a score below mean five semantic differential scales for positive questions and above mean for negative questions) of mental illness. Being above 28 years of age (AOR = 0.48 CI (0.23, 0.78)), private workers (AOR = 0.41 CI (0.19, 0.87)), and lack of mental health information were found to be associated with poor perception of mental illness (AOR = 0.133 CI (0.09, 0.20)). Absence of family history of mental illness was also found to be associated with poor perception of mental illness (AOR = 0.37 CI (0.21, 0.66)). Conclusions. Significant proportions of the community in Gimbi town were found to have poor perception of mental illness. Poor perception is common among old aged, less educated, private workers, those unable to access mental health information, and those with no family history of mental illness. Mental health education on possible causes, treatment options, and possible outcome of treatment to the community is required.